Impact of Candida Species on Clinical Outcomes in Patients with Suspected Ventilator-Associated Pneumonia - Marie-Soleil Delisle; David R Williamson; Martin Albert; Marc M Perreault; Xuran Jiang; Andrew G Day; Daren K Heyland (Canadian Respiratory Journal)
BACKGROUND: The significance of Candida species in respiratory tract (RT) secretions in critically ill patients is unclear.